Reversible phase transformation in proton conducting strandberg-type POM based metal organic material - Dey, Chandan; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
A Cu(II)-phenanthroline connected Strandberg-type polyoxometalate based proton conducting MOF, Cu3Mo5P2, that contains one dimensional parallel water channels has been reported. Cu3Mo5P2 shows proton conduction at room temperature as well as elevated temperature.